Nanomanaging Chronic Wounds with Targeted Exosome Therapeutics - Anita Yadav; Anu Sharma; Mohini Moulick; Subhadip Ghatak (Pharmaceutics)
Chronic wounds pose a significant healthcare challenge, impacting millions of patients worldwide and burdening healthcare systems substantially. These wounds often occur as comorbidities and are prone to infections. Such infections hinder the healing process, complicating clinical management and proving recalcitrant to therapy. The environment within the wound itself poses challenges such as lack of oxygen, restricted blood flow, oxidative stress, ongoing inflammation, and bacterial presence. Traditional systemic treatment for such chronic peripheral wounds may not be effective due to inadequate blood supply, resulting in unintended side effects. Furthermore, topical applications are often impervious to persistent biofilm infections. A growing clinical concern is the lack of effective therapeutic modalities for treating chronic wounds. Additionally, the chemically harsh wound microenvironment can reduce the effectiveness of treatments, highlighting the need for drug delivery systems that can deliver therapies precisely where needed with optimal dosages. Compared to cell-based therapies, exosome-based therapies offer distinct advantages as a cell-free approach for chronic wound treatment. Exosomes are of endosomal origin and enable cell-to-cell communications, and they possess benefits, including biocompatibility and decreased immunogenicity, making them ideal vehicles for efficient targeting and minimizing off-target damage. However, exosomes are rapidly cleared from the body, making it difficult to maintain optimal therapeutic concentrations at wound sites. The hydrogel-based approach and development of biocompatible scaffolds for exosome-based therapies can be beneficial for sustained release and prolong the presence of these therapeutic exosomes at chronic wound sites. Engineered exosomes have been shown to possess stability and effectiveness in promoting wound healing compared to their unmodified counterparts. Significant progress has been made in this field, but further research is essential to unlock their clinical potential. This review seeks to explore the benefits and opportunities of exosome-based therapies in chronic wounds, ensuring sustained efficacy and precise delivery despite the obstacles posed by the wound environment.